INDEKS KEPUASAN PENGGUNA LAYANAN: Menggeser Kepentingan Pelanggan ke Kepentingan Warga Negara - Bevaola Kusumasari (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2006)
The new public service recognizes that those who interact with government are not simply called customers but rather citizens. In government, citizens are not only customers, they are owners of the government, therefore citizens decide what is so important that the government will do. Today, citizens expect public services to meet standards not only such as timeliness and reliability in getting the service but also they should do the services be delivered fairly and with attention to fiscal responsibility as well. More important, citizens contemplate to have the opportunity to influence the services they receive as well as the quality of those services.